What is the reasonable option for elderly patients with incidental pancreatic cystic neoplasms? Follow‐up observation versus surgical resection. Issue 2 (21st January 2016) - Kim, Hyo Jung; Kim, Jae Seon; Lee, Jae Min; Joo, Moon Kyung; Lee, Beom Jae; Kim, Ji Hoon; Yeon, Jong Eun; Park, Jong‐Jae; Lee, Hong Sik; Byun, Kwan Soo; Kim, Chang Duck; Bak, Young‐Tae
Abstract : Aims: Pancreatic cystic neoplasms (PCN) with malignant potential are thought to be less aggressive than ordinary ductal adenocarcinoma, even in the setting of malignant transformation. Therefore, deciding whether or not to carry out surgery is very difficult, especially in elderly and asymptomatic patients, because of the high risk of perioperative morbidities. The aim of the present study was to examine clinical outcomes of PCN patients aged 65 years or older. Methods: This retrospective analysis included patients with incidentally detected PCN with follow‐up durations >1 year. Patients diagnosed with obvious simple cysts, pseudocysts or pancreatic cancer and patients with a history of pancreatic disease were excluded from the study. Results: The present study included 201 patients (older group 104 patients ≥65 years; younger group 97 patients <65 years). Surgical resections were carried out for 27 patients in the older group and 41 patients in the younger group. There were 133 patients who were followed up without surgery (mean follow‐up duration 41 months). Postoperative morbidity occurred in 22.2% of the patients in the older group and 21.9% of the patients in the younger group. Malignancy occurred in one patient in the older group and in two patients in the younger group. The PCN diameter increased in 20 patients during follow up: 16.9% of the older group and 12.5% of the younger group. Conclusions: The malignancy rate was very low in incidental PCN patients irrespective of age. Follow‐up observation without surgery appears to be a safe option in older patients with morbidity.Geriatr Gerontol Int 2017; 17: 256–261.